Enhanced nutrient and rainwater use efficiency in maize and soybean with secondary and micro nutrient amendments in the rainfed semi-arid tropics - Girish, C.; Suhas, P.W.; Kanwar, L.S.; Rajesh, C. (Informa UK Limited, 2015)
In view of widespread deficiencies, a long-term experiment was started at the International Crops Research Institute for the Semi-Arid Tropics, Patancheru, India in 2007 to identify economically efficient application strategy (full or 50% dose every or every second year) of sulphur (S) (30 kg ha?1), boron (B) (0.5 kg ha?1) and zinc (Zn) (10 kg ha?1). During the fourth year in 2010, balanced fertilization through adding S, B and Zn increased maize grain yield by 13–52% and soybean yield by 16–28% compared to nitrogen (N) and phosphorus (P) fertilization alone. Balanced nutrition increased N and P uptake, utilization and use efficiency for grain yield and harvest index indicating improved grain nutritional quality. The N, P plus 50% of S, B and Zn application every year recorded highest crop yields and N and P efficiencies indices and increased rainwater use efficiency with a benefit:cost ratio of 11.9 for maize and 4.14 for soybean. This study showed the importance of a deficient secondary nutrient S and micronutrients B, Zn in improving N and P use efficiency while enhancing economic food production.